2022
DOI: 10.1109/access.2022.3204671
|View full text |Cite
|
Sign up to set email alerts
|

PI Controller for Hybrid Biomass- Solar Photovoltaic- Wind in Microgrid: A Case Study of Mersing, Malaysia

Abstract: Renewable energy has become an alternative energy to replace fossil fuels in electric power generation systems to alleviate environmental problems in the future. Alongside the shift to renewable energy, microgrid technology has also evolved to integrate renewable energy into the power generation and distribution system. In addition, the issue of voltage stability is also a vital factor in sustaining microgrids with renewable energy integration to ensure system stability. Reports in earlier studies have include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Applying econometric models to analyze the relationship between the economy and RE, Afroz and Muhibbullah [ 85 ] demonstrated that a reduction in RE consumption accelerates economic growth whereas that for NRE decreases economic growth. Using an optimization model for a hybrid grid, Badruhisham et al [ 86 ] investigated the integration of a hybrid BM-Solar PV-Wind off-grid microgrid comprising a PI controller as the voltage control based on an actual input database at a location in a small rural town to support the voltage stability of the system. Employing the Bootstrap ARDL model, Suki et al [ 87 ] explored the role of green innovation and RE on carbon emissions and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Applying econometric models to analyze the relationship between the economy and RE, Afroz and Muhibbullah [ 85 ] demonstrated that a reduction in RE consumption accelerates economic growth whereas that for NRE decreases economic growth. Using an optimization model for a hybrid grid, Badruhisham et al [ 86 ] investigated the integration of a hybrid BM-Solar PV-Wind off-grid microgrid comprising a PI controller as the voltage control based on an actual input database at a location in a small rural town to support the voltage stability of the system. Employing the Bootstrap ARDL model, Suki et al [ 87 ] explored the role of green innovation and RE on carbon emissions and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Opposed to the mechanical torque, there is an electromagnetic torque T e that is generated due to the magnetic fields of the rotor and stator. This torque is calculated using Equation (10), where p is the number of PMSG poles, φ m is the constant magnetic flux of the rotor magnets, and i q is the component of the stator current in the q-direction.…”
Section: Wind System Description and Modelingmentioning
confidence: 99%
“…In [9], the implementation of a controller applied to a DCµG feed by a wind system, including a doubly fed induction generator, is described. In [10], a case study is presented in which the authors implement a PI controller for a hybrid insolated µG; the energy sources of this µG are biomass, solar photovoltaic, and wind. In [11], an energy management strategy for a grid-connected µG is presented; the primary renewable energy source of this µG is a wind turbine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proportional-integral controllers have the merits of easy design as well as structural simplicity. Many literatures have been reported regarding the control of solar energy system [3][4][5][6][7][8][9][10][11][12][13][14][15]. However, solar energy systems governed by proportional-integral controllers may be affected with uncertainties, like partial shading problem.…”
Section: Introductionmentioning
confidence: 99%